Local Community Participation in the Development of Ecological Tourism in West Bali National Park - Sunarta, I Nyoman (E-Journal of Tourism; Volume 2 Number 2 (September 2015), 2015)
Dependence of local communities on natural resources in the area of ??West Bali National Park (TNBB) showed low conservation awareness of local communities to support the area as ecological tourism resources, and showed lack of participation of the local community because of their powerlessness in decision-making and captures a wide range of benefits or contributions of ecological tourism. This study aims to determine the level of local participation in the development of products and markets of ecological tourism, by using deductive approach.During stage of analysis and synthesis, descriptive method is used to explain the causal link between the study variables. Since 2008, TNBB changed its repressive approach to community development that previously looked into persuasive public relations with BTNBB as " us vs. them " later changed into " we ", especially in the development of ecological tourism product, which is actualized in society called "Manuk Jegeg". Participation of local communities in the development of ecological tourism is not entirely the local community initiatives. So that kind of participation can be classified into functional types of participation. Participation is still a continuation of the existence of an external agent External interests of society. It is seen from the establishment of "Manuk Jegeg" community, where external parties are only facilitating and accommodating the aspirations of the community in decision making.
Keywords: participation, ecological tourism, “manuk jegeg”